Comparative biometry and morphometry of stomach and intestines of muong indigenous and vietnamese wild pigs - Pham, Hong Trang (2012)
Genetic studies have proven the diversity of Vietnamese indigenous pigs which is together with the Chinese strain providing the main genetic source of domesticated pig across East Asia. Moreover, the vestiges of wild pig ancestor of some Asian islands as well as Borneo have been found and still inhabit in center Asia. However, the genetic relationship between Vietnamese domestic and wild pigs has not been yet clearly defined. We hypothesized that after the long period of adaptation, the Vietnamese indigenous and wild pigs which are living in the same habitat may reveal some identical characters in morphology. On the top of genetic aspect, with regard to the evolution of the gastrointestinal system, we aim to assess the similarities and differences between Muong indigenous pigs and Vietnamese wild pig. Due to the protective nature and scarcity of procuring wild pigs, a total of 12 Muong indigenous pigs and nine Vietnamese wild pigs were studied. The tape and commercial scale have been used in recording biometric data with 0.1 cm and 0.1 g graduation marking. The morphometry of gastrointestinal tract has been examined by using the basic histological staining method Haematoxylin and Eosin (H&E). Different staining methods such as Periodic Acid Schiff (PAS), Alcian blue pH 2.5 (AB pH 2.5) and Orcein - Alcian blue (Orcein - AB) were employed in evaluating histochemical reaction of GI tract. The comparison of some selected biometric parameters indicates the marked difference; the body of the wild boars was 27.8% heavier and 31% longer than the domestic form (p<0.05); even the mass stomach of wild boar was statistically greater than that of Muong indigenous pigs (412.85 ± 15.21 vs. 271.72 ± 28.39) but the relative weight (to body weight) was not different reflecting the similar in ability of development. However, the dissimilarity in the shape of stomach may implies the difference in morphological structure; the Muong indigenous pig a presented higher relative weight of small intestine (5.2 vs. 4.8) but lower relative weight of large intestine (3.3 vs. 4.7); the wild boars revealed the shorter digestive tract but the difference was not significant (p≥0.05). Interestingly, the development of live body length, stomach mass, small and large intestine was highly correlated with live body weight (0.96<R2≤1). The histometry of the gastric gland region has reflected the identical structure with two out of three measured elements including the layers of tunica muscularis and tunica mucosa which were not statistically different (p≥0.05). On the other hand, the layer of submucosa was significantly thicker (p<0.05); apart from the presence of numerous loose connective tissues, this feature may contributed by the abundance of blood vessels, white adipose tissues and nervous plexus. The appearance of lymphoid follicles underneath the tubular gastric glands in the wild boars exceeded that of Muong indigenous pigs. This finding suggested that the different immune responses are the result of feeding behaviors as well as individually reactions.The small intestinal morphology and the thickness of the duodenum, jejunum and ileum and their muscularis externa, submucosa, inner mucosa, the height of villi and the depth of crypt were estimated. Only in the duodenum of the domestic pigs, the tunica muscular was significantly thicker (p<0.05) than that of the wild counterpart. By contrast, the tunica mucosa was only significant different in the last portion of small intestine between two studied subjects. Additionally, the submucosal layer gradually elevated in two lower segments of the small bowel and once again, the domestic pigs presented higher proportion of this element. The height of villus decreased throughout the small intestine; however, the villus of Vietnamese wild pig was higher (p<0.05) in the ileum. The depth of crypt shared the same falling feature but the significant different can be observed in the jejunum and ileum. Despite the similarities at the duodenum and jejunum, morphometry of the ileum was significantly different between the two subjects in four out of five studied factors (p<0.05). The most interesting finding was the quantity of duodenal goblet cell. Muong indigenous pigs possessed 2.88 times higher number of duodenal goblet cells compared to Vietnamese wild pigs. This result implied the differences of nutritional composition. This study has partially completed the biometrical picture of the two subjects apart from providing the morphological data of the stomach and small intestines of Vietnamese wild pigs and their domestic counterpart. It also paved the way as a reference for further zoological studies.